Comparison of analgesic efficacy of ultrasound-guided external oblique intercostal plane block and subcostal transversus abdominis plane block in patients undergoing upper abdominal surgery: A randomised clinical study - Shruti Shrey; Chandni Sinha; Abhyuday Kumar; Ajeet Kumar; Amarjeet Kumar; Sreehari Nambiar (Indian Journal of Anaesthesia)
Background and Aims: Upper abdominal surgeries are associated with severe postoperative pain. External oblique intercostal (EOI) block blocks both anterior and lateral cutaneous branches of intercostal nerves. We compared the postoperative analgesic efficacy of unilateral EOI block with conventional unilateral subcostal transversus abdominis plane (TAP) block. Methods: Fifty American Society of Anesthesiologists (ASA) I/II patients scheduled for upper abdominal surgery via subcostal incision were randomly assigned to receive either EOI block (Group E) or subcostal TAP block (Group T) with 25 mL of 0.2% ropivacaine. Postoperatively, these patients received intravenous (IV) fentanyl through a patient-controlled analgesia (PCA) pump with settings of demand-only mode. The primary outcome was the time to activation of PCA postoperatively. Secondary outcomes were 24-hour opioid consumption, pain scores (at 30 minutes and at 1, 2, 4, 6, 12, and 24 hours), patient satisfaction scores (48 hours), and block-related complications. Unpaired t-test and Mann-Whitney U test were used for analysis. A P value less than 0.05 was considered to be statistically significant. Results: Patients in Group E had an increased mean time of activation of PCA [610.28 [standard deviation (SD): 118.95)] minutes vs 409.68 (SD: 101.36) minutes] (P = 0.001). The 24-hour postoperative mean fentanyl consumption was 102.40 (SD: 25.70) μg in Group E versus 123.20 (SD: 34.38) μg in Group T (P = 0.019). Patients in Group E had better satisfaction scores (P < 0.001). Pain scores were better at 30 minutes and 6 hours. Conclusion: EOI block provides effective postoperative analgesia in upper abdominal surgeries as it prolongs the duration of PCA activation with a better patient satisfaction score.